The Effect of Anger on Criminal Decision-Making - Cimalanskaitė-Kazlauskienė, Violeta; Valickas, Gintautas (Teisė, 2023)
The article analyses the effect of the experience of anger on criminal decision-making, depending on the time spent assessing the situation. Based on a dual-process approach, an experiment was conducted. All participants (67 convicted adult males) examined fraud scenarios and made decisions about the actor’s consent/refusal to commit the crime under different conditions: with or without the arousal of anger, with limited or unlimited time for the evaluation. The results confirm that the anger experienced at the time of the decision taking impacts information processing. The anger felt during the decision is related to the orientation towards the difficulties experienced by the actor in the situation. Mild anger experienced during the decision with limited and unlimited time to assess the scenario is associated with Type 2 (rational, analytical) processing.
Keywords: Criminal decision-making; Experienced anger; Time pressure; Dual-process of information processing